Reading comprehension and learning of the english language at the basic level - Martel-Paredes, Víctor H. (2023)
The lie has fallen into disrepute. It is thought that you should always tell the truth and that turns you into a virtuous moral agent. Usually it is thought that Kant proposes an exhaustive and stubborn truth, however, it would have to prove the necessity and function of the lie within language, therefore the image of Cassandra will be taken, the Trojan princess who despite she always tell the truth nobody really believed in her. The possibility of a dialogue between Cassandra and Kant assumes the universality of the human condition.